2019
DOI: 10.1101/591586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure to maternal obesityper seprograms sex-differences in pancreatic islets of the offspring

Abstract: Maternal obesity increases type 2 diabetes (T2D) risk in the offspring. Given that nearly half of women of child-bearing age in many populations are currently overweight/obese, it is key that we improve our understanding of the impact of the in utero/early life environment on offspring islet function. Using a well-established mouse model of diet-induced obesity, we examined offspring islets before the onset of metabolic dysfunction. This allowed us to determine inherent changes, in males and females, which are… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Human and animal studies have demonstrated the important role of in-utero and early postnatal environments in modulating offspring islet insulin secretion (13)(14)(15)(16). This concept of the developmental origin of health and diseases (DOHaD) was first described by Dr. Barker and Dr. Osmond, where adults that experienced growth restriction during fetal life were found to have a higher rate of cardiovascular diseases during adulthood (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Human and animal studies have demonstrated the important role of in-utero and early postnatal environments in modulating offspring islet insulin secretion (13)(14)(15)(16). This concept of the developmental origin of health and diseases (DOHaD) was first described by Dr. Barker and Dr. Osmond, where adults that experienced growth restriction during fetal life were found to have a higher rate of cardiovascular diseases during adulthood (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…However, the sexspecific impact of maternal obesity exposure on insulin secretion in human offspring has not been studied extensively. Therefore, animal models have been used to delineate the specific impact of maternal obesity on offspring islet insulin secretion (16,26,27).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations